(untitled) (International Seven Journal of Multidisciplinary, 2024)
Introduction: The mandibular torus is an exostosis characterized by bone growth. It is frequently seen in male patients, with a prevalence in young adults and middle-aged patients. With regard to treatment, the literature advises against removing the mandibular torus; only in specific situations is intervention necessary. Aim: The aim of this study is to report a case of a female mandibular torus and to detail its removal. Methodology: Case report describing the anamnesis, medical history, oral clinical examination, imaging examination and the intervention chosen after analyzing all the data collected. Case report: A 74-year-old patient sought dental care complaining of dissatisfaction with her smile. A thorough clinical examination revealed the presence of a hard, lobular mass in the region of the lingual alveolar process of the mandible, covered by normal-looking mucosa. The patient reported discomfort and pain due to the presence of the mass. Based on the clinical examination and complementary imaging, the patient was diagnosed with a mandibular torus, and the decision was made to remove it because it would compromise her intended treatment. She was then advised to follow certain recommendations and was constantly monitored by the team. Conclusion: The study presented a case of mandibular torus that culminated in the effective removal of the bilateral mandibular torus, contributing to a better fit of the prosthesis, ensuring better adaptation, stability and retention of the prosthetic piece.